1993
DOI: 10.1007/bf00197138
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of bone destruction in rheumatoid arthritis: comparison with radiography

Abstract: Bony changes in forty-four knees of patients with clinically established rheumatoid arthritis (RA) were examined using magnetic resonance imaging (MRI) and plain film radiography. In all cases MRI was clearly superior to radiographs, demonstrating 25 marginal erosions and 42 subchondral cysts, while the number seen on radiographs was 3 and 8, respectively. These results emphasize the problems in visualizing bone erosions in large joints using plain films. MRI is the method of choice for detecting early changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 11 publications
(30 reference statements)
3
19
0
Order By: Relevance
“…MRI detected erosions in 92 finger joints (20%; 26 patients) in group 1 that were not detected by conventional radiography. Other investigators as well as our group have reported similar results for the wrists (24,25,(37)(38)(39), shoulders (40)(41)(42)(43), and knees of RA patients (26,(44)(45)(46) and for the sacroiliac joints of patients with spondylarthropathies (6,7,9).…”
Section: Backhaus Et Alsupporting
confidence: 72%
See 1 more Smart Citation
“…MRI detected erosions in 92 finger joints (20%; 26 patients) in group 1 that were not detected by conventional radiography. Other investigators as well as our group have reported similar results for the wrists (24,25,(37)(38)(39), shoulders (40)(41)(42)(43), and knees of RA patients (26,(44)(45)(46) and for the sacroiliac joints of patients with spondylarthropathies (6,7,9).…”
Section: Backhaus Et Alsupporting
confidence: 72%
“…In contrast to conventional radiography, MRI depicts early inflammatory changes in the joint, especially synovitis and tenosynovitis. Furthermore, MRI detects erosions earlier than conventional radiography (13,(23)(24)(25)(26)(27). The objective of the present study was to perform a prospective comparative investigation of clinical signs and findings on conventional radiography, 3-phase bone scintigraphy, ultrasound, and MRI using precontrast and dynamic postcontrast examination of the dominant hand in patients with arthritis who do not have typical radiologic signs of destructive arthritis in that hand and to compare the findings with those in patients with typical radiologic signs of erosions.…”
mentioning
confidence: 99%
“…Bone oedema is another important MRI feature in inflammatory joint diseases [5,7,8,9,10,11], and it has been suggested to be a forerunner of bone erosion [9]. Bone oedema has been observed in more than half of the patients with rheumatoid arthritis [9,12].…”
mentioning
confidence: 99%
“…Although these techniques have a higher sensitivity for disease detection, our MR-based method with the use of FR-targeted Gd-chelates has the advantage of a higher spatial resolution, which allows a better delineation of individual joint components (14,20,22,(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MR is not associated with any radiation exposure. Although standard gadopentetate-enhanced MR imaging provides a high sensitivity for the detection of arthritis, it provides only a limited specificity (17)(18)(19)(20), because the enhancement of inflammatory tissues overlaps with the enhancement patterns of normal joints and other pathologic processes (17,21,22). New FR-based gadolinium (Gd) chelates are expected to improve the sensitivity and specificity of MR imaging for the diagnosis of arthritis, similar to the radiotracers mentioned above.…”
Section: Introductionmentioning
confidence: 96%